Structure, Diameter Increment, and Cutting Cycle of Residual Stand in Logged-Over Forest in East Kalimantan - M. Taufan Tirkaamiana; Lailan Syaufina (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
This study aims to determine the structure, diameter increment, and cutting cycle estimation of residual stand for commercial species at log over forest managed with a selective cutting and line planting system (TPTJ) at PT Balikpapan Wana Lestari East Kalimantan, Indonesia. The residual stand parameter (tree amount, diameter, and increment) measurement was conducted at the log over area for 1 year, 2 years, and 3 years at the inter-planting line in TPTJ block from 3 PUP (Permanent measuring plot) which each with a size of 100 m x 100 m (1 ha). The result presents residual stand structure at the inter-planting line based on diameter class in the 'J' upside-down form indicates the larger diameter class, the smaller tree amount. The average diameter increment of the residual stand at the inter-planting line for commercial species is 1.04 cm/yr, and non-commercial is 0.65 cm/yr. The estimated cutting cycle is 19 years for commercial species with a cutting diameter limit of 40 cm up. The potential of stands in the inter-planting line can be expected to produce logging at the end of the cycle, besides the stand in the planted line, including superior species and having significant increments. Keywords: cutting diameter limit, diameter increment, nucleus tree, stand structure